Neutralization method for detecting the incidence of color perception changes after cataract surgery. Issue 4 (April 2015) - Miyata, Akira
Abstract : Purpose : To evaluate and compare the incidence of cyanopsia using the neutralization method in eyes in which clear or yellow intraocular lenses (IOLs) were implanted. Setting : Miyata Eye Clinic, Hiroshima, Japan. Design : Retrospective comparative study. Methods : Patients who had cataract surgery with the implantation of a monofocal IOL were enrolled in the study. Group 1 had implantation of a clear IOL (Acrysof SA60AT, Sensar AR40e, N4‐18B). Group 2 had implantation of a yellow IOL (AF‐1 YA60BB, AN‐6). A control group comprised healthy patients. The detection and degree of cyanopsia were evaluated using white gradation cards (1 white [W] and 5 white gradation cards with increasing intensity of yellow tint [Y1, Y2, Y3, Y4, and Y5]) (neutralization method). Results : The study comprised 57 patients in Group 1, 96 in Group 2, and 41 in the control group. All patients in the control group selected the W, Y1, or Y2 cards as white. Cyanopsia was then defined as the perception of Y3, Y4, and Y5 as white. One month postoperatively, cyanopsia occurred significantly more frequently in Group 1 than in Group 2 (14.5% versus 4.9%) ( P = .049). There was no significant difference at 3 months (9.1% versus 5.2%) ( P > .05). In Group 1, cyanopsia was more frequent in eyes with monocular IOL implantation than in eyes with binocular IOL implantation (22.2% versus 2.7%; P = .035). Conclusion : The incidence of cyanopsia evaluated with the neutralization method was higher with clear IOLs than with yellow IOLs. In monocular implantation, yellow IOLs are recommended to avoid cyanopsia. Financial Disclosure : The author has no financial or proprietary interest in any material or method mentioned.